A self seeded first level track trigger for ATLAS - Schöning, André (Journal of Instrumentation, 2012)
For the planned high luminosity upgrade of the Large Hadron Collider, aiming to increase the instantaneous luminosity to 5 × 10 34 cm −2 s −1 , the implementation of a first level track trigger has been proposed. This trigger could be installed in the year 2021 along with the complete renewal of the ATLAS inner detector. The fast readout of the hit information from the Inner Detector is considered as the main challenge of such a track trigger. Different concepts for the implementation of a first level trigger are currently studied within the ATLAS collaboration. The so called "Self Seeded" track trigger concept exploits fast frontend filtering algorithms based on cluster size reconstruction and fast vector tracking to select hits associated to high momentum tracks. Simulation studies have been performed and results on efficiencies, purities and trigger rates are presented for different layouts.
Gesehen am 09.07.2018
Keywords: Konferenzschrift